Formação acadêmica e produção científica docente em descrição arquivística: um estudo a partir dos cursos de graduação em arquivologia do Brasil - Rego, Laura Maria do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Although professional training in Archival Science in Brazil dates back to 1911, with the regulatory decree of the National Archive, in 1977 the first university courses on Archival Sciences were implemented in the country, including instructors with diverse backgrounds. However, in the last twenty years, with the expansion of undergraduate courses on Archival Science in Brazil, universities started to require professionals with specific education and experience in the field, something that was taking into account in the allocation of subjects to instructors. In this scenario, the research question is to what extent the subject specificity in the Archival Science instructors' education is related to scientific production. Thus, focusing on the area of archival description, we studied the Lattes curricula of instructors responsible for courses in Archival Science in Brazil, seeking to identify and analyze their education and the scientific production of these instructors, identifying trends and theoretical lines in the area in order to understand to what extent the subject specificity of the instructor's education is related to his/her scientific production. The goal to identify the degree of correspondence between academic education and scientific production based on previous studies of Guimarães (2003) in the field of Library Science. Therefore, we performed a documental exploratory study, through the theoretical review of the trends in archival description, and the analysis of the syllabi of the courses, identifying disciplines that relate to this subject and to the body of instructors. Based on this review, it was possible to reach a set of twenty-three courses, taught by eighteen instructors. Regarding the instructors' education at the undergraduate level, we identified the prevalence (60%) of Archival Science, together with, in lesser incidence, History. At master level, the prevalence (56%) is Information Science, while in...

Embora a capacitação profissional em Arquivologia, no Brasil, remonte a 1911, com o decreto de regulamentação do Arquivo Nacional, apenas em 1977 foram implantados, no país, os primeiros cursos universitários de Arquivologia, contando com docentes de diversificadas áreas. No entanto, nos últimos 20 anos, com a expansão dos cursos de graduação em Arquivologia, no Brasil, as universidades passaram a requerer profissionais com formação específica e experiência na área, aspecto levado em conta na atribuição de disciplinas aos docentes. À vista de tal cenário, questiona-se até que ponto a especificidade temática da formação do docente em áreas específicas da Arquivologia se encontra relacionada à produção científica. Assim, e tendo como foco a área de descrição arquivística, realizou-se um estudo dos currículos Lattes dos docentes responsáveis por disciplinas na referida área, em cursos de Arquivologia, no Brasil, buscando: identificar e analisar sua formação e produção científica; identificar tendências e linhas teóricas na área; compreender até que ponto a especificidade temática da formação do docente está relacionada com a sua produção científica; averiguar o grau de articulação entre formação acadêmica e produção científica docente tendo por base estudos anteriores de Guimarães (2003), no campo da Biblioteconomia. Para tanto, foi realizado um estudo exploratório documental, por meio de revisão teórica sobre as correntes da descrição arquivística e análise das estruturas curriculares dos cursos, identificando as disciplinas que se relacionam com essa temática, bem como o corpo docente que trabalha com a mesma. Com base nesse levantamento, foi possível chegar a um conjunto de vinte três disciplinas, ministradas por um conjunto de dezoito docentes. Relativamente à formação docente em nível de graduação, identificou-se a predominância (60%) do curso de Arquivologia, ao que...
Keywords: Arquivologia - Brasil - Estudo e ensino; Professores universitários - Formação; Pesquisa; College teachers Training of